The Relationship Between Growing Altitude and Oil Yield and Fatty Acid Composition of VCO from Coconuts in West Timor - Jasman Jasman; Idalia Norceb; Angnes Amtahanb; Yosep Lawab (International Journal of Mathematics and Science Education, 2025)
The aim of this study is to show the yield, quality, and the fatty acids composition of VCO produced from coconut growing in several location having different altitudes in West Timor. In addition, it also determined the correlation between the yield, quality, and the composition at one side and the altitude at other side. The coconut samples were taken from six locations at different altitudes. Virgin coconut oil is fermented using baker's yeast (Saccharomyces cerevisiae). The oil yield was calculated based on the oil volume ratio to the coconut cream volume, and the composition of fatty acid was then determined by a gas chromatography-mass spectrophotometer (GC-MS). The results showed that the quality of VCO obtained in this study is very good based on Indonesian National Standard (SNI) No. 7381:2008. The higher the growing location of coconut, the oil yield decreases slightly, the peroxide number increases slightly, the water content and free fatty acids are decrease. The correlation between the altitude of the coconut growing location and the fatty acid composition: lauric acid (strong and positive); palmitic and oleic acids (strong and negative); linoleic acid (very strong and negative); capric, myristic, and stearic acids (very weak and negative).